Influence of weather parameters on growth and yield of black pepper (Piper nigrum L.) - Sushna K (Department of Agricultural Meteorology, College of Horticulture, 2016)
Black pepper (Piper nigrum L.) (Family: Piperaceae) is a perennial vine grown for its berries extensively used as spice and in medicine. India is one of the major producer, consumer and exporter of black pepper in the world. It is cultivated to a large extent in Kerala, Karnataka and Tamil Nadu and to a limited extent in Maharashtra, North eastern states and Andaman & Nicobar Islands. Black pepper is a plant of humid tropics requiring high rainfall and humidity. The hot and humid climate of sub mountainous tracts of Western Ghats is ideal for its cultivation. It grows successfully between 20° North and South latitudes and up to 1500 m above sea level. The crop tolerates temperatures between 10°and 40°C. The favourable temperature range is 23 - 32°C and the ideal temperature is around 28°C. The present study consisted of two experiments. In the first experiment statistical analysis of the yield data which was collected from three research stations of Kerala Agricultural University viz, Pepper unit of College of Horticulture, llanikkara, Pepper Research Station,Panniyur and Regional Agricultural Research Station, Ambalavayal for the years 1997-2015, 2001-2015, 1991-2015 respectively were analysed to study the weather relationship on the yield of black pepper. Relative humidity in the morning and rainfall during spike initiation, spike enlargement and berry development stages negatively influenced the yield of black pepper, whereas the same condition during the spike emergence stage had positive influence on the yield. Minimum temperature during April and November positively affected the yield. The weather variables which had significant correlation on yield were taken for four cell analysis to find out the plausibility of above average yield. The results showed that the decrease in relative humidity during morning and rainfall during the berry development resulted in 90% increase in yield at Ambalavayal. The decrease in morning relative humidity and rainfall during spike initiation stage favoured 60% above average yield at Vellanikkara. Increase in minimum temperature and decrease in morning relative humidity caused 83% above average yield at Panniyur. The second experiment was conducted during 2015 in the pepper unit of Department of Plantation crops and Spices, College of Horticulture, Vellanikkara, Thrissur. The important growth parameters of pepper such as number of newly produced leaves, laterals, orthotropic branches, adventitious roots, internodal length of main and laterals and leaf area development were showed influence on growth and yield of pepper.Correlation between weather parameters, maximum temperature, minimum temperature,morning relative humidity, soil temperature, evening relative humidity, wind speed, bright sunshine hours, rainfall, rainy days, evaporation, solar radiation, vapour pressure, soil moisture and plant characters were estimated for all the black pepper varieties.Rainfall and relative humidity were favourable for the production of new leaves, nodes,laterals, orthotropic branches and adventitious roots, whereas bright sunshine hours and maximum temperature had negative influence on these characters. Optimum range of rainfall for the growth of pepper was found about 100-150 mm in case of this experiment. Optimum range of other weather parameters such as maximum temperature, minimum temperature, RHI, RHII and soil temperature were 30-320C, 23-250C, 80-90%, 60-70% and 28-300C respectively. Leaf area development was negatively influenced by Growing Degree Day (GDD). Favourable climatic factors were found to have a deciding role in the yield of pepper. Knowledge about the relationship between crop growth stages and weather parameters are very important to maximise pepper production.